Analisis Pengaruh Perspektif Manajemen Laba Terhadap Earnings Response Coefficient (ERC) dengan Moderasi Skor Pengungkapan ESG - Jauza Nada Alfiyah; Khomsiyah Khomsiyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted to examine the effect of earnings management on market responses to earnings announcements, as well as to test the influence of ESG (Environmental, Social, and Governance) disclosure scores as corporate reputation insurance, which is assumed to affect market responses to managed earnings. The main focus is to determine whether a firm's commitment to sustainability can mitigate the potential negative impact of managed earnings on the Earnings Response Coefficient (ERC). This study utilizes 195 observation samples from non-financial public companies in Indonesia listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 observation period, employing the OLS (Ordinary Least Square) method with robust standard errors. The results indicate that earnings management during this period does not directly affect market reactions to the company's announced earnings; however, the company's ESG disclosure score has a significant impact on market reactions. Thus, it is concluded that ESG disclosure by companies serves as a positive signal that is highly valued by the market in the current era of sustainable investment.